Antifouling coating composition

By using antifouling coating compositions containing metal ester-based hydrolyzable polymers, medetomidine, brominated pyrrolidnitrile and pyridinethione copper, the problem of poor adhesion of the existing antifouling coating film in high-fouling sea areas and repair processes is solved, and excellent standing and dynamic antifouling properties are achieved, as well as good adhesion to deteriorated coating films are achieved.

CN119654383AActive Publication Date: 2025-03-18CHUGOKU MARINE PAINTS
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202380056106.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-02-28
Filing Date
2023-07-27
Publication Date
2025-03-18
Estimated Expiration
2043-07-27

AI Technical Summary

Technical Problem

The existing hydrolytic antifouling coating film is easily adhered to animals such as barnacles, bryozoos, and syringosoma during low-speed/low operation in high-fouling sea areas, and is difficult to directly adhere to the deteriorated antifouling coating film during the repair process, and there is a problem of peeling.

Method used

An antifouling coating composition containing a metal ester group, medetomidine, brominated pyrrolidnitrile and copper pyridinethione as essential ingredients is used to form an excellent antifouling coating film through a balanced combination of these components.

Benefits of technology

It has achieved excellent antifouling properties after both standing and dynamic immersion, and can be well adhered to various primer films and medium coating films, and has excellent adhesion to deteriorated antifouling coating films, avoiding peeling problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119654383A_ABST
    Figure CN119654383A_ABST
Patent Text Reader

Abstract

Provided is an antifouling coating composition which is capable of forming an antifouling coating film that has both excellent stood antifouling properties and excellent stood antifouling properties after long-term dynamic immersion, and also has excellent adhesion and peeling resistance to a primer coating film and an intermediate coating film, and also has excellent adhesion to an old antifouling coating film. The antifouling coating composition according to the present invention contains (A) a hydrolyzable polymer containing a metal ester group, (B) medetomidine, (C) bromo-pyrrolic nitrile, (D) copper pyrithione, and (E) a linear or branched alkyl carboxylic acid having 4-30 carbon atoms. The polymer (A) contains a structural unit derived from a metal ester group-containing monomer (a1) represented by formula (1) and / or a structural unit derived from a metal ester group-containing monomer (a2) represented by formula (2). In formula (1), R11 each independently represents a monovalent group containing a terminal ethylenically unsaturated group, and M represents a copper atom or a zinc atom. In formula (2), R21 represents a monovalent group containing a terminal ethylenically unsaturated group, R22 represents a monovalent organic group having 1-30 carbon atoms and not containing a terminal ethylenically unsaturated group, and M represents a copper atom or a zinc atom. # imgabs0 # imgabs1 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an antifouling coating composition, an antifouling coating film, a substrate with an antifouling coating film, a method for producing a substrate with an antifouling coating film, and an antifouling method for a substrate. More specifically, the present invention relates to an antifouling coating composition containing specific components such as a hydrolyzable polymer and an antifouling agent, etc. Background Art

[0002] As a method for preventing aquatic organisms from fouling a substrate such as a ship, a method of forming an antifouling coating film containing a hydrolyzable polymer on the surface of the substrate is widely used. As such an antifouling coating film, various studies have been conducted on antifouling coatings containing polymers containing metal ester groups.

[0003] For example, Patent Document 1 discloses an antifouling coating composition (patent claims, etc.) containing a polymer containing a metal ester group and at least medetomidine and optionally further containing an antifouling agent such as copper pyrithione, 2-(p-chlorophenyl)-3-cyano-4-bromo-5-trifluoromethylpyrrole (also known as bromopyrrolecarbonitrile (Tralopyril)), and describes that such an antifouling coating composition can form an "antifouling coating film having a stable coating film consumption rate and exhibiting excellent antifouling properties for a long time in ships, underwater structures, etc."

[0004] Patent document 2 discloses an antifouling coating composition (patent claims, etc.) containing a hydrolyzable polymer containing a metal ester group, a tertiary carboxylic acid component containing versatic acid, and an antifouling agent component such as 4-bromo-2-(4-chlorophenyl)-5-(trifluoromethyl)-1H-pyrrole-3-carbonitrile (also known as bromopyrrolecarbonitrile), and states that such an antifouling coating composition can form "an antifouling coating film having excellent long-term coating film consumption, antifouling properties, weather resistance and other coating film properties, and is not prone to foaming (bubbling) even when formed on a deteriorated coating film."

[0005] Patent document 3 discloses an antifouling coating composition containing a hydrolyzable polymer containing a metal ester group, a specific amount of zinc oxide and medetomidine (patent claims, etc.), and states that such an antifouling coating composition can form an "antifouling coating film that maintains high antifouling properties for a long time and has excellent damage resistance."

[0006] Patent Document 4 discloses an antifouling coating composition (patent claims, etc.) containing a specific amount of a resin having a specific metal carboxylate structure, and at least medetomidine and 4-bromo-2-(4-chlorophenyl)-5-(trifluoromethyl)-1H-pyrrole-3-carbonitrile (also known as bromopyrrolecarbonitrile), and optionally further containing an antifouling agent such as copper pyrithione, and describes that such an antifouling coating composition can form "a coating film that can ensure long-term antifouling properties even without using cuprous oxide."

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent document 1: WO2011 / 118526

[0010] Patent Document 2: WO2016 / 084769

[0011] Patent Document 3: WO2018 / 003135

[0012] Patent Document 4: Japanese Patent Application Publication No. 2020-100794 Summary of the invention

[0013] Problems to be solved by the invention

[0014] In recent years, even the existing hydrolyzable antifouling coatings (e.g., the hydrolyzable antifouling coatings containing medetomidine described in Patent Documents 1 to 4) that are believed to have a certain level of antifouling performance, have been reported to have confirmed the attachment of animal species such as barnacles, bryozoans, and cyprids during low speed / low operation in high-fouling waters and during the mooring period waiting for docking. Therefore, especially in the outfitting process when building a new ship, a coating that has both static antifouling properties and antifouling properties when moored after sailing (static antifouling properties after long-term dynamic immersion) is required. In addition, due to the impact of the global epidemic of COVID-19, not only the number of ships moored for a long time and ships with reduced operating rates has increased, but also the risk of fouling of ships has increased due to abnormal weather and changes in the marine environment. In order to cope with the risk of fouling of such ships, it is strongly required to develop a coating composition that has excellent antifouling properties even for ships moored for a long time, and even for long-term ships moored after sailing.

[0015] On the other hand, the construction of new ships generally adopts the hull block construction method. In the installation process (hull block joining process), when the coating surface around the weld is roughened by a power tool, the existing antifouling coating has the problem of peeling and scattering of the coating film, which is presumably caused by the adhesion to the base anticorrosion coating, its coating properties (hardness), etc. In addition, the antifouling coating that has passed the service life period is usually pulled to the land (for example: dock) for repair (repair) coating of the ship and other structures. However, in this repair coating, not only can the ship not be used, but the use fee of the dock is also high, so it is strongly required to complete it in a short time from an economic point of view. Therefore, it is important not only to have adhesion to the base coating such as the sound anticorrosion coating before use, but also to have excellent adhesion to the antifouling coating (old antifouling coating) after deterioration of the repair object (that is, it is not necessary to remove the old antifouling coating).

[0016] The present invention aims to provide an antifouling coating composition capable of forming an antifouling coating film having (1) excellent antifouling properties in both static antifouling properties generally required of antifouling coating films and static antifouling properties after long-term dynamic immersion required of ships at anchor after operation (antifouling coating films that have deteriorated, deteriorated or been consumed); and (2) excellent adhesion to a sound anticorrosion coating film (primer coating film or mid-coat coating film) before use (before immersion in seawater), peeling resistance of the coating film during power tool handling, and adhesion to an old antifouling coating film after use (after immersion in seawater).

[0017] Methods used to solve problems

[0018] The present inventors have found that an antifouling coating composition that can solve the above-mentioned problems can be prepared by using a specific hydrolyzable polymer containing a metal ester group, three specific antifouling agents, namely medetomidine, bromopyrrolecarbonitrile and copper pyrithione, and a specific alkyl carboxylic acid, such as versatile carbonic acid, as essential components, thereby completing the present invention. Although these components are used in existing antifouling coating compositions individually or in combination in part, it is unexpected that by using all of these components in combination, an antifouling coating composition that satisfies various properties as described above in a balanced manner and can solve new problems can be obtained; in particular, even similar components that are treated as equivalents or substitutes in existing antifouling coating compositions can achieve effects that cannot be achieved by selecting other components by selecting specific components. Although a collection of prior art may be able to satisfy individual properties or several properties, the antifouling coating composition of the present invention that can simultaneously and balancedly satisfy various properties without damaging specific properties by selecting specific components for combination is not easy to obtain for those skilled in the art other than the present inventors.

[0019] That is, the present invention includes at least the following matters.

[0020] [Item 1]

[0021] An antifouling coating composition comprising a hydrolyzable polymer containing a metal ester group (A), medetomidine (B), bromopyrrole carbonitrile (C), copper pyrithione (D), and a linear or branched alkyl carboxylic acid having 4 to 30 carbon atoms (E).

[0022] The polymer (A) includes a structural unit derived from a metal ester group-containing monomer (a1) represented by the following formula (1) and / or a structural unit derived from a metal ester group-containing monomer (a2) represented by the following formula (2).

[0023]

[0024] (In formula (1), R 11 Each independently represents a monovalent group containing a terminal ethylenically unsaturated group, and M represents a copper atom or a zinc atom. )

[0025]

[0026] (In formula (2), R 21 represents a monovalent group containing a terminal ethylenically unsaturated group, R 22 represents a monovalent organic group having 1 to 30 carbon atoms and not containing a terminal ethylenically unsaturated group, and M represents a copper atom or a zinc atom.

[0027] [Item 2]

[0028] The antifouling coating composition according to item 1, wherein the polymer (A) comprises a metal ester group-containing monomer (a1) represented by the following formula (1').

[0029]

[0030] (In formula (1'), R 12 Each independently represents a hydrogen atom or a methyl group, and M represents a copper atom or a zinc atom. )

[0031] [Item 3]

[0032] The antifouling coating composition according to item 1 or 2, wherein the alkyl carboxylic acid (E) is versatic acid.

[0033] [Item 4]

[0034] The antifouling coating composition according to any one of items 1 to 3, wherein the content of the medetomidine (B) is 0.1 to 100% by mass, the content of the bromopyrrolecarbonitrile (C) is 10 to 1700% by mass, based on 100% by mass of the copper pyrithione (D), and

[0035] The content of copper pyrithione (D) is 0.5 to 12% by mass based on 100% by mass of the solid content of the antifouling coating composition.

[0036] [Item 5]

[0037] An antifouling coating film formed from the antifouling coating composition according to any one of items 1 to 4.

[0038] [Item 6]

[0039] A substrate with an antifouling coating film, comprising a substrate and the antifouling coating film according to item 5.

[0040] [Item 7]

[0041] The substrate with an antifouling coating according to Item 6, wherein the substrate is selected from the group consisting of ships, underwater structures, and fishery materials.

[0042] [Item 8]

[0043] A method for manufacturing a substrate with an antifouling coating, comprising:

[0044] A step (1) of applying the antifouling coating composition according to any one of items 1 to 4 onto a substrate or impregnating the substrate into a substrate to obtain a coated body or an impregnated body; and

[0045] A step (2) of drying the coated body or impregnated body.

[0046] [Item 9]

[0047] An antifouling method for a substrate, comprising the step of forming the antifouling coating film according to item 5 on at least a portion of the substrate.

[0048] Effects of the Invention

[0049] The antifouling coating composition of the present invention can form an antifouling coating film which is excellent not only in normal static antifouling properties but also in static antifouling properties after long-term dynamic immersion, and which has excellent adhesion and peeling resistance to various primer coating films and mid-coat coating films, and excellent adhesion to various old antifouling coating films. This can also cope with the new performance requirements for antifouling coating films of ships and the like that have become apparent due to environmental changes in recent years. DETAILED DESCRIPTION

[0050] In the present specification, “(meth)acrylic acid” means “acrylic acid or methacrylic acid” or “acrylic acid and methacrylic acid” according to the context, and “(meth)acrylate” means “acrylate or methacrylate” or “acrylate and methacrylate” according to the context.

[0051] The upper limit value and the lower limit value (for example, regarding the content of a component) described in this specification can be arbitrarily combined to set a numerical range.

[0052] In this specification (especially in Examples), "part" as a unit added after a numerical value means "part by mass" unless otherwise specified.

[0053] -Antifouling coating composition-

[0054] The antifouling coating composition of the present invention contains a hydrolyzable polymer (A) containing a metal ester group (sometimes referred to as "polymer (A)" or "component (A)" in the present specification), medetomidine (B) (sometimes referred to as "component (B)" in the present specification), bromopyrrolecarbonitrile (C) (sometimes referred to as "component (C)" in the present specification), copper pyrithione (D) (sometimes referred to as "component (D)" in the present specification), and a linear or branched alkyl carboxylic acid having 4 to 30 carbon atoms (E) (sometimes referred to as "alkyl carboxylic acid (E)" or "component (E)" in the present specification).

[0055] <Polymer (A)>

[0056] The polymer (A) contains structural units derived from a metal ester group-containing monomer (a1) (sometimes referred to as "monomer (a1)" in this specification) and / or structural units derived from a metal ester group-containing monomer (a2) (sometimes referred to as "monomer (a2)" in this specification). Any one of the polymers (A) may be used, or two or more structural units derived from the monomer (a1) and / or structural units derived from the monomer (a2) may be used, each of which has different structures, ratios, etc. The polymer (A) preferably contains at least a structural unit derived from the monomer (a1), that is, contains a structural unit derived from the monomer (a1), or contains both a structural unit derived from the monomer (a1) and a structural unit derived from the monomer (a2).

[0057] Monomer (a1)

[0058] The metal ester group-containing monomer (a1) is a monomer represented by the following formula (1). The monomer (a1) may be any one kind or may be two or more kinds.

[0059]

[0060] In formula (1), R 11 Each independently represents a monovalent group containing a terminal ethylenically unsaturated group (CH2=C<), and M represents a copper atom or a zinc atom.

[0061] R 11The number of carbon atoms of the terminal ethylenically unsaturated group is preferably 2-50, more preferably 2-30, further preferably 2-10, particularly preferably 2-6.

[0062] R 11 Although the ethylenically unsaturated group may be contained at a position other than the terminal, it is more preferable that the ethylenically unsaturated group be contained only at the terminal.

[0063] R 11 Preferably, it is an organic group containing a terminal ethylenically unsaturated group (referred to as "terminal ethylenically unsaturated organic group" in this specification). As the terminal ethylenically unsaturated organic group, for example, an unsaturated aliphatic hydrocarbon group whose structure may be partially substituted by an ester bond, an amide bond or an ether bond can be cited. As specific examples of such terminal ethylenically unsaturated organic groups, there can be cited: a group obtained by removing a carboxyl group from an aliphatic unsaturated monocarboxylic acid containing a terminal ethylenically unsaturated group, such as acrylic acid (another name: 2-acrylic acid), methacrylic acid (another name: 2-methyl-2-acrylic acid), 3-butenoic acid, 4-pentenoic acid, 10-undecenoic acid, (meth)acryloyloxyalkylcarboxylic acid [e.g., 3-(meth)acryloyloxypropionic acid, 3-(meth)acryloyloxy-2-methylpropionic acid]; and a group obtained by removing a carboxyl group from an aliphatic unsaturated dicarboxylic acid having a terminal ethylenically unsaturated group, such as itaconic acid. As the terminal ethylenically unsaturated organic group, a group obtained by removing a carboxyl group from an aliphatic unsaturated monocarboxylic acid containing a terminal ethylenically unsaturated group is more preferred, a group obtained by removing a carboxyl group from acrylic acid, methacrylic acid or (meth)acryloyloxyalkylcarboxylic acid is further preferred, and a group obtained by removing a carboxyl group from acrylic acid or methacrylic acid is particularly preferred.

[0064] As the monomer (a1), a monomer represented by the following formula (1') is preferred (also referred to as "monomer (a1')" in this specification). The monomer (a1') corresponds to two R 11 The terminal ethylenically unsaturated organic groups are all groups obtained by removing a carboxyl group from acrylic acid or methacrylic acid.

[0065]

[0066] In formula (1'), R 12 Each independently represents a hydrogen atom or a methyl group, and M represents a copper atom or a zinc atom.

[0067] Examples of the monomer (a1) include zinc diacrylate, zinc dimethacrylate, zinc methacrylate, zinc di(3-acryloyloxypropionate), zinc di(3-methacryloyloxypropionate), zinc di(3-(meth)acryloyloxy-2-methylpropionate), copper diacrylate, copper dimethacrylate, copper methacrylate, copper di(3-acryloyloxypropionate), copper di(3-methacryloyloxypropionate), and copper di(3-(meth)acryloyloxy-2-methylpropionate). Among these, zinc diacrylate, zinc dimethacrylate, and zinc methacrylate are preferred because an antifouling coating having sufficient antifouling properties can be easily obtained. It should be noted that zinc diacrylate, zinc dimethacrylate, zinc methacrylate, copper diacrylate, copper dimethacrylate, and copper methacrylate are monomers (a1′).

[0068] Monomer (a2)

[0069] The metal ester group-containing monomer (a2) is a monomer represented by the following formula (2). The monomer (a2) may be any one kind or may be two or more kinds.

[0070]

[0071] In formula (2), R 21 represents a monovalent group containing a terminal ethylenically unsaturated group (CH2=C<), R 22 represents a monovalent organic group having 1 to 30 carbon atoms and having no terminal ethylenically unsaturated group, and M represents a copper atom or a zinc atom.

[0072] About R 21 For technical matters related to the terminal ethylenically unsaturated group of 11 Technical matters related to terminal ethylenically unsaturated groups.

[0073] As R 22 Examples of such organic groups include aliphatic hydrocarbon groups having 1 to 30 carbon atoms, alicyclic hydrocarbon groups having 3 to 30 carbon atoms, aromatic hydrocarbon groups having 6 to 30 carbon atoms, etc. (referred to as "non-terminal ethylenically unsaturated organic groups" in this specification) that do not contain a terminal ethylenically unsaturated group. The non-terminal ethylenically unsaturated organic group may further contain a substituent (e.g., a hydroxyl group).

[0074] The aliphatic hydrocarbon group in the non-terminal ethylenically unsaturated organic group may be either linear or branched, and may be either a saturated aliphatic hydrocarbon group or an unsaturated aliphatic hydrocarbon group (as long as it does not contain a terminal ethylenically unsaturated group). The number of carbon atoms in the aliphatic hydrocarbon group is 1 to 30, preferably 1 to 28, more preferably 1 to 26, and further preferably 1 to 24. The aliphatic hydrocarbon group may be substituted with an alicyclic hydrocarbon group or an aromatic hydrocarbon group.

[0075] The alicyclic hydrocarbon group in the non-terminal ethylenically unsaturated organic group may be a saturated alicyclic hydrocarbon group or an unsaturated alicyclic hydrocarbon group. The number of carbon atoms in the alicyclic hydrocarbon group is 3 to 30, preferably 4 to 20, more preferably 5 to 16, and further preferably 6 to 12. The alicyclic hydrocarbon group may be substituted by an aliphatic hydrocarbon group or an aromatic hydrocarbon group.

[0076] The number of carbon atoms of the aromatic hydrocarbon group in the non-terminal ethylenically unsaturated organic group is 6 to 30, preferably 6 to 24, more preferably 6 to 18, and further preferably 6 to 10. The aromatic hydrocarbon group may be substituted with an aliphatic hydrocarbon group or an alicyclic hydrocarbon group.

[0077] R 22 Preferably, it is an organic acid residue derived from a monobasic acid. Specific examples thereof include groups obtained by removing a carboxyl group from organic acids such as tertiary carbonic acid, palmitic acid, stearic acid, isostearic acid, oleic acid, linoleic acid, linolenic acid, abietic acid, neoabietic acid, pimaric acid, dehydroabietic acid, 12-hydroxystearic acid, and cycloalkane acid. Among these, groups obtained by removing a carboxyl group from abietic acid, tertiary carbonic acid, or cycloalkane acid are preferred, and groups obtained by removing a carboxyl group from abietic acid or tertiary carbonic acid are more preferred. It should be noted that tertiary carbonic acid is a general term for a mixture of carboxylic acids having 9 to 11 carbon atoms, and mainly 10 carbon atoms, and having many branches.

[0078] As the monomer (a2), a monomer represented by the following formula (2') is preferred (also referred to as "monomer (a2')" in this specification). The monomer (a2') corresponds to R in the monomer (2). 22 The terminal ethylenically unsaturated organic group is a monomer obtained by removing a carboxyl group from acrylic acid or methacrylic acid.

[0079]

[0080] In formula (2'), R 23 represents a hydrogen atom or a methyl group, R 24 With R in formula (2) 22 The meanings are the same, and M represents a copper atom or a zinc atom.

[0081] Examples of the monomer (a2) include rosin zinc 3-(meth)acryloyloxypropionate, zinc versatate 3-(meth)acryloyloxypropionate, rosin zinc (meth)acrylate, zinc versatate (meth)acrylate, zinc cyclohexanecarboxylate, rosin copper 3-(meth)acryloyloxypropionate, copper versatate 3-(meth)acryloyloxypropionate, rosin copper (meth)acrylate, copper versatate (meth)acrylate, and copper cyclohexanecarboxylate. It should be noted that rosin zinc (meth)acrylate, zinc versatate (meth)acrylate, zinc cyclohexanecarboxylate, rosin copper (meth)acrylate, copper versatate (meth)acrylate, and copper cyclohexanecarboxylate are monomers (a2′).

[0082] Other monomers

[0083] The polymer (A) may further contain monomers other than the monomer (a1) and the monomer (a2) which are copolymerizable with the monomer (a1) and / or the monomer (a2) as required. Examples of such arbitrary monomers include monomers which do not contain a metal ester group and have an ethylenically unsaturated group, for example, an organosiloxane block monomer (a3) ​​(sometimes referred to as "monomer (a3)" in this specification); (meth) acrylic acid ester or its ester (a4) (sometimes referred to as "monomer (a4)" in this specification); and a vinyl compound (a5) (sometimes referred to as "monomer (a5)" in this specification).

[0084] Monomer (a3)

[0085] The monomer (a3), namely, the organosiloxane block-containing monomer (a3) ​​is a monomer represented by the following formula (3). The monomer (a3) ​​may be any one kind or two or more kinds.

[0086]

[0087] In formula (3), R 31 , R 32 and R 33 Each independently represents a monovalent hydrocarbon group, X each independently represents a (meth)acryloyloxyalkyl group or a mercaptoalkyl group, m is 1 or more, n is 0 or more, p and q each independently represent 0 or 1, and n+p+q is 1 or more.

[0088] As R 31 , R 32 and R 33 The hydrocarbon group may be a linear, branched or cyclic alkyl group or an aryl group. The alkyl group preferably has 1 to 12 carbon atoms, more preferably 1 to 8 carbon atoms, and still more preferably 1 to 4 carbon atoms. The aryl group preferably has 6 to 14 carbon atoms, more preferably 6 to 10 carbon atoms. From the viewpoint of ease of polymerization, R 31 , R32 and R 33 Each is independently an alkyl group such as methyl or butyl.

[0089] Examples of X include (meth)acryloxyalkyl groups such as (meth)acryloxyethyl, (meth)acryloxypropyl, and (meth)acryloxybutyl; and mercaptoalkyl groups such as mercaptomethyl, mercaptoethyl, mercaptopropyl, and mercaptobutyl. From the viewpoint of uniform polymerization, X is preferably a (meth)acryloxyalkyl group, and from the viewpoint of reducing the viscosity of the copolymer (A) and facilitating handling, a mercaptoalkyl group is preferably.

[0090] m and n represent (SiR 32 2O)、(SiXR 33 The average number of added moles of m+n is preferably 2 or more. That is, the organosiloxane block-containing monomer (a3) ​​is preferably a polyorganosiloxane block-containing monomer.

[0091] It should be noted that, in this specification, as shown in formula (3), when two or more different repeating units are recorded in parallel between [], it means that these repeating units can be repeated in any order of random, alternating or block. That is, for example, in the case of formula -[Y3-Z3]- (herein, Y and Z represent repeating units respectively), it can be a random shape such as -YYZYZZ-, it can also be an alternating shape such as -YZYZYZ-, it can also be a block shape such as -YYYZZZ- or -ZZZYYY-.

[0092] As a first embodiment of the monomer (a3), a monomer (a31) in which n is 0, p is 1, and q is 0 can be cited. When the copolymer (A) contains a structural unit derived from such a monomer (a31), it is preferred because, for example, the antifouling coating composition can easily form an antifouling coating film with excellent antifouling properties. From the viewpoint of ease of polymerization, etc., m in the monomer (a31) is preferably 3 or more, more preferably 5 or more, and is preferably 200 or less, more preferably 70 or less.

[0093] As the monomer (a31), for example, commercially available products manufactured by JNC Corporation include "FM-0711" (one-terminal methacryloxyalkyl-modified organopolysiloxane, number average molecular weight: 1000), "FM-0721" (one-terminal methacryloxyalkyl-modified organopolysiloxane, number average molecular weight: 5000), and "FM-0725" (one-terminal methacryloxyalkyl-modified organopolysiloxane, number average molecular weight: 10000); Commercially available products manufactured by Koshi Chemical Industry Co., Ltd. include "X-22-174ASX" (single-end methacryloyloxyalkyl-modified organic polysiloxane, functional group equivalent: 900 g / mol), "KF-2012" (single-end methacryloyloxyalkyl-modified organic polysiloxane, functional group equivalent: 4600 g / mol), and X-22-2426 (single-end methacryloyloxyalkyl-modified organic polysiloxane, functional group equivalent: 12000 g / mol).

[0094] As a second embodiment of the monomer (a3), a monomer (a32) in which n is 0, p and q are 1 can be cited. When the copolymer (A) contains a structural unit derived from such a monomer (a32), it is preferred because, for example, the antifouling coating composition has excellent repairability, that is, an antifouling coating film with excellent adhesion to an old antifouling coating film after use (after immersion in seawater) can be easily formed. From the viewpoint of ease of polymerization, etc., m in the monomer (a32) is preferably 3 or more, more preferably 5 or more, preferably 200 or less, and more preferably 70 or less.

[0095] As the monomer (a32), for example, commercially available products “FM-7711” (organopolysiloxane modified with methacryloxyalkyl groups at both ends, number average molecular weight: 1000), “FM-7721” (organopolysiloxane modified with methacryloxyalkyl groups at both ends, number average molecular weight: 5000), and “FM-7725” (organopolysiloxane modified with methacryloxyalkyl groups at both ends, number average molecular weight: 10000) manufactured by JNC Corporation; commercially available products “X-22-164” (organopolysiloxane modified with methacryloxyalkyl groups at both ends, functional group equivalent: 190 g / mol), and “X-22-164AS” (organopolysiloxane modified with methacryloxyalkyl groups at both ends, functional group equivalent: 190 g / mol) manufactured by Shin-Etsu Chemical Co., Ltd. , functional group equivalent: 450g / mol), "X-22-164A" (methacryloxyalkyl modified organic polysiloxane at both ends, functional group equivalent: 860g / mol), "X-22-164B" (methacryloxyalkyl modified organic polysiloxane at both ends, functional group equivalent: 1630g / mol), "X-22-164C" (methacryloxyalkyl modified organic polysiloxane at both ends, functional group equivalent: 2370g / mol), "X-22-164E" (methacryloxyalkyl modified organic polysiloxane at both ends, functional group equivalent: 3900g / mol), "X-22-167B" (mercaptoalkyl modified organic polysiloxane at both ends, functional group equivalent: 1670g / mol), etc.

[0096] As a third embodiment of the monomer (a3), a monomer (a33) in which n is 1 or more can be cited. When the copolymer (A) contains a structural unit derived from such a monomer (a33), it is preferred because, for example, the viscosity of the antifouling coating composition is reduced and there is a tendency for the handling to become easier. In the monomer (a33), m is preferably 50 to 1000, and n is preferably 1 to 30.

[0097] As the monomer (a33), for example, commercially available products “KF-2001” (side chain mercaptoalkyl-modified organopolysiloxane, functional group equivalent: 1900 g / mol) and “KF-2004” (side chain mercaptoalkyl-modified organopolysiloxane, functional group equivalent: 30000 g / mol) manufactured by Shin-Etsu Chemical Co., Ltd. can be used.

[0098] Monomer (a4)

[0099] The monomer (a4), that is, the (meth)acrylic acid ester or its ester (a4), is a compound represented by the following formula (4). The monomer (a4) may be any one kind or two or more kinds.

[0100]

[0101] In formula (4), R41 represents a monovalent group containing an ethylenically unsaturated group, R 42 represents a hydrogen atom, an alkyl group, an aryl group, an alkoxyalkyl group, a hydroxyalkyl group or a glycidyl group.

[0102] As a first embodiment of the monomer (a4), R 42 A monomer (a41) having a hydrogen atom, such as (meth)acrylic acid. When the copolymer (A) contains such a monomer (a41), the obtained antifouling coating composition has excellent adhesion to the old antifouling coating film after use (after immersion in seawater), low viscosity, and excellent coating workability, and the formed antifouling coating film tends to have a high coating film consumption.

[0103] As a second embodiment of the monomer (a4), R 42 A monomer (a42) which is an alkyl group or an aryl group. 42 The alkyl group may have any structure of linear, branched or cyclic, and the number of carbon atoms is preferably 1 to 20, more preferably 1 to 12, and further preferably 1 to 6. When the copolymer (A) contains such a monomer (a42), the antifouling coating film formed from the obtained antifouling coating composition tends to be able to suppress the coating film consumption to an appropriate renewal rate without significantly impairing the antifouling property, and tends to also have excellent scratch resistance and / or crack resistance.

[0104] Specific examples of the monomer (a42) include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 3,5,5-trimethylhexyl (meth)acrylate, lauryl (meth)acrylate, hexadecyl (meth)acrylate, stearyl (meth)acrylate, phenyl (meth)acrylate, and benzyl (meth)acrylate. For example, at least one selected from the group consisting of methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, and cyclohexyl (meth)acrylate is preferably used as the monomer (a42).

[0105] As a third embodiment of the monomer (a4), R 42 A monomer (a43) which is an alkoxyalkyl group. 42The alkoxyalkyl group may have any structure of linear, branched or cyclic, and the number of carbon atoms (the total number of carbon atoms contained in the alkyl group in the alkoxy group and the number of carbon atoms contained in the alkyl group) is preferably 1 to 20, more preferably 1 to 12, and further preferably 1 to 6. When the copolymer (A) contains such a monomer (a43), the antifouling coating film formed from the obtained antifouling coating composition tends to maintain an appropriate degree of coating film consumption for a long period of time.

[0106] Specific examples of the monomer (a43) include: 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, 3-methoxy-n-propyl (meth)acrylate, 2-propoxyethyl (meth)acrylate, 2-butoxyethyl (meth)acrylate, isobutoxybutyl diglycol (meth)acrylate, 2-phenoxyethyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, ethoxypolyethylene glycol (meth)acrylate, butoxypolyethylene glycol (meth)acrylate, and phenoxypolyethylene glycol (meth)acrylate. For example, 2-methoxyethyl (meth)acrylate is preferably used as the monomer (a43).

[0107] As a fourth embodiment of the monomer (a4), R 42 A monomer (a44) which is a hydroxyalkyl group. 42 The hydroxyalkyl group may have any structure of linear, branched or cyclic, and preferably has 1 to 20 carbon atoms, more preferably 1 to 12, and further preferably 1 to 6. When the copolymer (A) contains such a monomer (a44), the antifouling coating film formed from the obtained antifouling coating composition tends to have a high degree of coating film consumption.

[0108] Specific examples of the monomer (a44) include hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate.

[0109] As a fifth embodiment of the monomer (a4), R 42 The monomer (a45) is a glycidyl group, for example, glycidyl (meth)acrylate. When the copolymer (A) contains such a monomer (a45), the antifouling coating film formed from the obtained antifouling coating composition tends to have a high coating film consumption.

[0110] From the viewpoint that the antifouling coating film formed from the obtained antifouling coating composition can appropriately adjust the coating film consumption degree and tends to have excellent scratch resistance and / or crack resistance, the polymer (A) preferably contains the monomer (a42) and / or the monomer (a43) among the above-mentioned monomers (a4).

[0111] Monomer (a5)

[0112] Examples of the monomer (a5), namely, the vinyl compound, include styrene, α-methylstyrene, vinyl acetate, vinyl benzoate, vinyl toluene, acrylonitrile, vinyl pyridine, vinyl pyrrolidone, and vinyl chloride. The monomer (a5) may be any one or two or more.

[0113] Ratio of structural units

[0114] The types and ratios of the structural units derived from the monomer (a1) and / or the monomer (a2) contained in the polymer (A) and other monomers used as necessary can be appropriately adjusted in consideration of the effects of the present invention, other technical matters, and the like.

[0115] For example, the ratio of the structural unit derived from the monomer (a1) and / or the structural unit derived from the monomer (a2) is preferably 5% by mass or more, more preferably 7% by mass or more, and further preferably 9% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, and further preferably 30% by mass or less, relative to 100% by mass of all the structural units in the copolymer (A).

[0116] In addition, the polymer (A) preferably contains at least a structural unit derived from a (meth)acrylate or an ester thereof (a4) in addition to the structural unit derived from the monomer (a1) and / or the structural unit derived from the monomer (a2), and may further contain a structural unit derived from an organic siloxane block-containing monomer (a3).

[0117] When the polymer (A) contains a structural unit derived from the organosiloxane-containing block monomer (a3), the ratio thereof is preferably 5% by mass or more, more preferably 8% by mass or more, and is preferably 20% by mass or less, more preferably 15% by mass or less, relative to 100% by mass of all the structural units in the copolymer (A).

[0118] When the polymer (A) contains a structural unit derived from a (meth)acrylate or an ester thereof (a4), the ratio thereof is preferably 3% by mass or more, more preferably 5% by mass or more, and is preferably 95% by mass or less, more preferably 80% by mass or less, and particularly preferably 70% by mass or less, relative to 100% by mass of all the structural units in the copolymer (A).

[0119] When the polymer (A) contains a structural unit derived from a vinyl compound (a4), the ratio thereof is preferably 3% by mass or more, more preferably 5% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, and particularly preferably 30% by mass or less, relative to 100% by mass of all the structural units in the copolymer (A).

[0120] It should be noted that the ratio of each structural unit in the copolymer (A) can be measured by nuclear magnetic resonance spectroscopy (NMR), gas chromatography-mass spectrometry (GC-MS) and the like according to conventional methods, or can be calculated from the usage of each monomer used when synthesizing the copolymer (A). In addition, all the constituent units in the copolymer (A) do not include structural units derived from polymerization initiators and chain transfer agents.

[0121] The number average molecular weight (Mn) and weight average molecular weight (Mw) of the polymer (A) can be appropriately adjusted in such a manner that the effect of the present invention is achieved to a desired degree, and in consideration of the viscosity of the obtained antifouling coating composition, storage stability, coating film consumption (dissolution rate, renewal) of the obtained antifouling coating film, etc. The Mn of the polymer (A) is preferably 500 or more, more preferably 700 or more, and preferably 100,000 or less, more preferably 50,000 or less. The Mw of the copolymer (A) is preferably 1,000 or more, more preferably 1,200 or more, particularly preferably 1,500 or more, and preferably 150,000 or less, more preferably 10,000 or less, and particularly preferably 7,000 or less.

[0122] It should be noted that Mn and Mw can be determined by measuring by gel permeation chromatography according to a conventional method and converting them to standard polystyrene. For more specific measurement methods and conditions of Mn and Mw, reference can be made to the Examples described below.

[0123] Content of ingredient (A)

[0124] The content of the polymer (A) can be appropriately adjusted according to the type and characteristics of the component so that the effect of the present invention can be achieved to a desired degree, and in consideration of the coating workability of the obtained antifouling coating composition and other technical matters. The content of the polymer (A) is, for example, preferably 10% by mass or more, more preferably 15% by mass or more, and preferably 40% by mass or less, more preferably 35% by mass or less, relative to 100% by mass of the solid content of the antifouling coating composition.

[0125] It should be noted that in the present specification, the "solid content" of each component (for example, components (A) to (E), oxidized polyethylene wax as an anti-sagging agent / anti-settling agent (G), fatty acid amide wax, etc.) or the antifouling coating composition of the present invention or each component contained therein means the component after removing the volatile components contained as a solvent in each component or the antifouling coating composition of the present invention. Such solid content can be calculated in the form of a ratio of the mass of a substance obtained by drying each component or the antifouling coating composition of the present invention in a hot air dryer at 108°C for 3 hours to the mass of each component or the antifouling coating composition of the present invention according to a conventional method. More specifically, according to JIS K 5601-1-2: 2008, 1±0.1 g of the object to be measured is weighed into a flat bottom dish, and a metal wire of known mass is uniformly spread on the bottom surface, and dried at 108°C under 1 atmosphere for 3 hours. The mass of the metal wire is subtracted from the obtained heated residue to obtain a value of mass percentage, and the calculation is performed. It should be noted that, with respect to the product of each component, when the numerical value in terms of solid content is shown on a label, catalog, etc., the numerical value may be regarded as the solid content of the component. In addition, when the ratio composition (the type and amount of each component and the solid content of each component) of the antifouling coating composition of the present invention is known by the above-mentioned measurement method, the numerical value calculated based on the ratio composition may be regarded as the solid content of the antifouling coating composition of the present invention.

[0126] <Medetomidine (B)>

[0127] Medetomidine (B), systematic name (+ / -)4-[1-(2,3-dimethylphenyl)ethyl]-1H-imidazole is a compound represented by the following structural formula. It should be noted that medetomidine (B) is a racemic form of (+)4-[1-(2,3-dimethylphenyl)ethyl]-1H-imidazole and (-)4-[1-(2,3-dimethylphenyl)ethyl]-1H-imidazole (an arbitrary ratio, such as a mixture of approximately equal amounts). Medetomidine (B) has optical isomerism, and it can be only one of them or a mixture of any ratio. In addition, medetomidine (B) can also use imidazole In this case, imidazole can be used as a raw material for preparing the antifouling coating composition of the present invention. The imidazole salts, adducts with metals, etc. can also be formed in the antifouling coating composition or antifouling coating film of the present invention. Salts, addition products with metals, etc.

[0128] <Bromopyrrolecarbonitrile (C)>

[0129] Bromopyrrolecarbonitrile (C), systematic name 4-bromo-2-(4-chlorophenyl)-5-(trifluoromethyl)-1H-pyrrole-3-carbonitrile, 2-(p-chlorophenyl)-3-cyano-4-bromo-5-trifluoromethylpyrrole is a compound represented by the following structural formula.

[0130]

[0131] <Copper pyrithione (D)>

[0132] Copper (D) pyrithione, systematically named bis[1,2-dihydro-2-thiopyridin-1-ol]copper (II), is a compound represented by the following structural formula.

[0133]

[0134] In formula (D), R 3 Each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, a cyclic alkyl group, an alkenyl group, an aryl group, an alkoxy group or a halogenated alkyl group, and M represents a copper atom. 3 Preferred is a hydrogen atom.

[0135] It should be noted that the antifouling coating composition of the present invention contains at least medetomidine (B), bromopyrrolecarbonitrile (C) and copper pyrithione (D) as antifouling agents. Even if only these three antifouling agents are used, a certain level of excellent antifouling performance can be exerted. One or more other antifouling agents can also be used in appropriate amounts as needed. Examples of the antifouling agent other than medetomidine (B), bromopyrrolecarbonitrile (C) and copper pyrithione (D) include cuprous oxide, metal pyrithione other than copper pyrithione (D) (e.g., zinc pyrithione), 4,5-dichloro-2-n-octyl-4-isothiazolin-3-one (also known as DCOIT), pyridinetriphenylborane, 4-isopropylpyridinediphenylmethylborane, N,N-dimethyl-N'-(3,4-dichlorophenyl)urea (also known as diuron), N-(2,4,6-trichlorophenyl)maleimide, 2,4,5,6-tetrachloroisophthalonitrile, 2-methylthio-4-tert-butylamino-6-cyclopropylamino-1,3,5-triazine (also known as Cyb utryne), bis(dimethyldithiocarbamoyl)ethylenebis(dithiocarbamate)zinc (also known as Polycarbamate), chloromethyl n-octyl disulfide, N,N'-dimethyl-N'-phenyl-(N-fluorodichloromethylthio)sulfonamide (also known as Dichlofluanid), tetraalkylthiuram disulfide (also known as TMTD), zinc dimethyldithiocarbamate (also known as Ziram), zinc ethylenebis(dithiocarbamate), 2,3-dichloro-N-(2',6'-dimethylphenyl)maleimide, 2,3-dichloro-N-(2'-ethyl-6'-methylphenyl)maleimide, etc.

[0136] However, cuprous oxide is an antifouling agent with a high load on the environment, and the antifouling coating composition of the present invention can exert excellent antifouling properties for a long time without using cuprous oxide. The content of cuprous oxide in the solid content of the antifouling coating composition of the present invention is preferably 10% by mass or less, more preferably 5% by mass or less, further preferably 1% by mass or less, further preferably 0.5% by mass or less, and particularly preferably substantially free of cuprous oxide. It should be noted that substantially free of cuprous oxide means that cuprous oxide is not intentionally added, and does not exclude the case where a small amount of cuprous oxide is contained as an impurity.

[0137] Content of components (B), (C) and (D)

[0138] The contents of medetomidine (B), bromopyrrolecarbonitrile (C) and copper pyrithione (D) can be appropriately adjusted so that the effects of the present invention are achieved to a desired extent, while taking into account the coating workability of the resulting antifouling coating composition and other technical matters.

[0139] For example, the content of medetomidine (B) is preferably 0.1% by mass or more, more preferably 1% by mass or more, and is preferably 100% by mass or less, more preferably 80% by mass or less, further preferably 50% by mass or less, and particularly preferably 10% by mass or less, relative to 100% by mass of copper pyrithione (D).

[0140] The content of bromopyrrolecarbonitrile (C) is preferably 10% by mass or more, more preferably 25% by mass or more, and is preferably 1700% by mass or less, more preferably 1500% by mass or less, further preferably 1200% by mass or less, further preferably 1000% by mass or less, and particularly preferably 100% by mass or less, relative to 100% by mass of copper pyrithione (D).

[0141] The content of copper pyrithione (D) is preferably 0.5% by mass or more, more preferably 1.0% by mass or more, and further preferably 3.0% by mass or more, and is preferably 12% by mass or less, more preferably 11% by mass or less, further preferably 10% by mass or less, and particularly preferably 8% by mass or less, relative to 100% by mass of the solid content of the antifouling coating composition.

[0142] <Alkyl carboxylic acid (E)>

[0143] Examples of the linear or branched alkyl carboxylic acid (E) having 4 to 30 carbon atoms include versatile carbonic acid, palmitic acid, stearic acid, and isostearic acid. Among these, versatile carbonic acid is preferred. Versatile carbonic acid is a mixture of branched alkyl carboxylic acids having 5 to 15 carbon atoms, mainly 9 to 11 carbon atoms, and particularly 10 carbon atoms. Alkyl carboxylic acids (E) may be used alone or in combination of two or more.

[0144] The alkyl carboxylic acid (E) may form a metal ester (eg, copper ester). The metal ester may be formed before the production of the antifouling coating composition, or may be formed by a reaction with other coating components during the production of the antifouling coating composition.

[0145] It should be noted that rosin (rosins such as gum rosin, wood rosin, and tall oil rosin, and rosin derivatives such as hydrogenated rosin and disproportionated rosin) is a mixture of abietic acid and its isomers having three ring structures containing conjugated double bonds and a carboxyl group, and although it is a monocarboxylic acid, it does not belong to the "straight-chain or branched alkyl carboxylic acid having 4 to 30 carbon atoms". In addition, cycloalkane acid, salicylic acid, etc. are also compounds having a ring structure and a carboxyl group, and although they are monocarboxylic acids, they do not belong to the "straight-chain or branched alkyl carboxylic acid having 4 to 30 carbon atoms".

[0146] Content of ingredient (E)

[0147] The content of the alkyl carboxylic acid (E) can be appropriately adjusted in consideration of the effects of the present invention, etc., depending on the type and properties of the component. The content of the alkyl carboxylic acid (E) is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and is preferably 10% by mass or less, more preferably 7% by mass or less, relative to 100% by mass of the solid content of the antifouling coating composition.

[0148] <Optional Ingredients>

[0149] The antifouling coating composition of the present invention may further contain components other than polymer (A), medetomidine (B), bromopyrrole carbonitrile (C), copper pyrithione (D) and alkyl carboxylic acid (E) as needed. As such optional components, for example, pigment (F), anti-sagging agent / anti-settling agent (G), solvent (H), plasticizer (I), adhesive component (J), etc. can be listed. Wetting dispersants, dehydrating agents, etc. can also be listed as optional components. These optional components are not necessary to achieve the effects of the present invention, but can be components that are naturally required or commonly used when implementing the antifouling coating composition, components that can easily exert or enhance the effects of the present invention, or components used to achieve effects other than the present invention.

[0150] <Pigment(F)>

[0151] The antifouling coating composition of the present invention may contain a pigment (F) for the purpose of coloring the coating film, hiding the base, and / or adjusting the coating film strength to be appropriate. The pigment (F) may be used alone or in combination of two or more.

[0152] Examples of the pigment (F) include: zinc oxide, zinc phosphate, talc, mica, clay, potassium feldspar, calcium carbonate, kaolin, alumina white, white carbon, aluminum hydroxide, magnesium carbonate, barium carbonate, barium sulfate (e.g., precipitated barium sulfate), calcium sulfate (e.g., calcined gypsum), zinc sulfide and other body pigments; and coloring pigments such as red iron oxide (red iron oxide), titanium white (titanium oxide), yellow iron oxide, carbon black, naphthol red, and phthalocyanine blue.

[0153] When the antifouling coating composition of the present invention contains a pigment (F), the content thereof can be appropriately adjusted depending on the purpose, the type of the component, etc., and is preferably 1 to 40% by mass based on 100% by mass of the solid content of the composition.

[0154] <Anti-sagging agent / anti-settling agent (G)>

[0155] The antifouling coating composition of the present invention may contain an anti-sagging agent / anti-settling agent (G) for the purpose of adjusting the viscosity of the composition, etc. The anti-sagging agent / anti-settling agent (G) may be used alone or in combination of two or more.

[0156] Examples of the anti-sagging agent / anti-settling agent (G) include organoclay waxes (e.g., stearates, lecithin salts, and alkyl sulfonates of Al, Ca, and Zn), organic waxes (e.g., polyethylene wax, oxidized polyethylene wax, fatty acid amide wax, and hydrogenated castor oil wax), mixtures of organoclay waxes and organic waxes, and synthetic fine powder silica. Examples of such anti-sagging agent / anti-settling agent (G) include commercially available products such as "Dispalon 305", "Dispalon 4200-20", "Dispalon A630-20X", and "Dispalon 6900-20X" manufactured by Kusumoto Chemicals Co., Ltd. and "ASA D-120" manufactured by Ito Oil Manufacturing Co., Ltd.

[0157] When the antifouling coating composition of the present invention contains an anti-sagging agent / anti-settling agent (G), the content thereof can be appropriately adjusted depending on the purpose, the type of the component, etc., and is, for example, preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and preferably 10% by mass or less, more preferably 3% by mass or less, relative to 100% by mass of the solid content of the composition.

[0158] <Solvent (H)>

[0159] For the purpose of adjusting the viscosity of the composition, the antifouling coating composition of the present invention may contain a solvent (H) such as water or an organic solvent. It should be noted that the antifouling coating composition of the present invention can be prepared using a liquid containing the copolymer (A) obtained when synthesizing the copolymer (A). In this case, the solvent contained in the liquid, the solvent added when mixing the copolymer (A) with other essential components (B) to (E) and optional components as required, etc. are equivalent to the solvent (H). Only one solvent (H) may be used, or two or more solvents may be used. As the solvent (H), an organic solvent is preferred.

[0160] Examples of the organic solvent include aromatic organic solvents such as xylene, toluene, and ethylbenzene; ketones such as methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; aliphatic (having 1 to 10 carbon atoms, preferably about 2 to about 5 carbon atoms) monohydric alcohols such as ethanol, isopropanol, n-butanol, isobutanol, and propylene glycol monomethyl ether; and ester solvents such as ethyl acetate and butyl acetate.

[0161] When the antifouling coating composition of the present invention contains a solvent (H), the content thereof can be appropriately adjusted depending on the purpose, the type of the component, etc., and is preferably 0 to 50% by mass based on 100% by mass of the composition.

[0162] <Plasticizer (I)>

[0163] The antifouling coating composition of the present invention may contain a plasticizer (I) for the purpose of imparting plasticity to the antifouling coating film to be formed, etc. The plasticizer (I) may be used alone or in combination of two or more.

[0164] Examples of the plasticizer (I) include chlorinated paraffin, normal paraffin, tricresyl phosphate (TCP), dioctyl phthalate (DOP), and diisodecyl phthalate (DIDP), and chlorinated paraffin and TCP are preferred.

[0165] Chlorinated paraffin may have a linear or branched molecular structure, and may be in a liquid state or a solid state (eg, powder) at room temperature (eg, 23° C.).

[0166] The average number of carbon atoms in one molecule of the chlorinated paraffin is preferably 8 or more, more preferably 10 or more, and preferably 30 or less, more preferably 26 or less. When the average number of carbon atoms is less than 8, the effect of suppressing the generation of cracks in the formed antifouling coating may be insufficient, while when the average number of carbon atoms is more than 30, the hydrolyzability (coating film consumption, renewal, and polishing washability) of the formed antifouling coating may be too low, resulting in poor antifouling properties.

[0167] The viscosity of the chlorinated paraffin (unit: poise, measurement temperature: 25°C) is preferably 1 or more, more preferably 1.2 or more. The specific gravity (25°C) is preferably 1.05 g / cm 3 More preferably, 1.10 g / cm 3 Above, and preferably 1.80 g / cm 3 Below, more preferably 1.70 g / cm 3 the following.

[0168] The chlorination rate (chlorine content) of the chlorinated paraffin is usually 35 to 70% by mass, preferably 35 to 65% by mass, when the chlorinated paraffin is taken as 100% by mass.

[0169] When the antifouling coating composition of the present invention contains a plasticizer (I), the content thereof is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and preferably 10% by mass or less, more preferably 5% by mass or less, based on 100% by mass of the solid content of the antifouling coating composition of the present invention, from the viewpoint of being able to well maintain the plasticization properties of the antifouling coating film.

[0170] <Binder component (J)>

[0171] The antifouling coating composition of the present invention may contain a binder component (J) for the purpose of imparting water resistance, crack resistance, strength, etc. to the formed antifouling coating film. It should be noted that the binder component (J) refers to the component other than the polymer (A) in the binder component. The binder component (J) may be used alone or in combination of two or more.

[0172] Examples of the binder component (J) include polyester polymers, (meth) acrylic polymers (copolymers), vinyl polymers (copolymers), terpene phenol resins, petroleum resins, and ketone resins. Among these, polyester polymers, (meth) acrylic polymers (copolymers), vinyl polymers (copolymers), and petroleum resins are preferred, and polyester polymers and petroleum resins are more preferred.

[0173] When the antifouling coating composition of the present invention contains a binder component (J), the content thereof can be appropriately adjusted depending on the purpose, the type of the component, etc., and is preferably 0.1 to 40% by mass based on 100% by mass of the solid content of the composition.

[0174] <Method for preparing antifouling coating composition>

[0175] The antifouling coating composition of the present invention can be prepared by the same means (apparatus, method, conditions, etc.) as for a conventional antifouling coating composition using components (A) to (E) and other optional components as required. Specifically, it can be prepared by the following method: after synthesizing the copolymer (A), the obtained copolymer (A) (solution), medetomidine (B), bromopyrrolecarbonitrile (C), copper pyrithione (D) and alkyl carboxylic acid (E) and other optional components as required are added to a container all at once or in sequence, and stirred and mixed.

[0176] -Antifouling coating-

[0177] The antifouling coating film of the present invention is formed by the antifouling coating composition of the present invention. The antifouling coating film of the present invention is formed by drying the antifouling coating composition of the present invention, as in the case where the existing antifouling coating film is formed by the existing antifouling coating composition. However, the antifouling coating film of the present invention is not limited to the antifouling coating film just formed by the antifouling coating composition of the present invention, and the antifouling coating film deteriorated due to use is also included in the antifouling coating film of the present invention. Regarding the antifouling coating film of the present invention, the antifouling coating film just formed contains the same substances as the antifouling coating composition of the present invention except for the volatile components such as the solvent lost due to drying, etc., and the antifouling coating film after use contains the same substances as the antifouling coating composition of the present invention except for the volatile components and a part of the components lost (released) due to the volatilization of the antifouling performance.

[0178] The thickness of the antifouling coating of the present invention is not particularly limited and can be set within an appropriate range according to the properties (e.g., coating consumption rate) and application (type of substrate, usage period, etc.) of the antifouling coating of the present invention. For example, the thickness in the immediately formed state is preferably 30 to 1000 μm.

[0179] -Substrate with antifouling coating-

[0180] The substrate with an antifouling coating film of the present invention comprises a substrate and the antifouling coating film of the present invention. The antifouling coating film of the present invention is usually formed on a substrate and used as the substrate with an antifouling coating film.

[0181] The substrate is not particularly limited, as long as it is a substrate that can form the antifouling coating of the present invention and can exert its function, and examples thereof include: ships (e.g., hull plates of large steel ships such as container ships, oil tankers, bulk carriers, fishing boats, FRP ships, wooden ships, yachts, etc., including any of new ships or repaired ships), fisheries or other marine materials (e.g., ropes, fishing nets, fishing gear, floats, buoys, diving suits, diving goggles, oxygen cylinders, swimsuits, torpedoes), underwater structures (e.g., oil pipelines, water pipes, circulating water pipes, water supply and drainage outlets of thermal power plants and nuclear power plants, submarine cables, seawater utilization equipment (seawater pumps, etc.), giant floating bodies, coastal roads, submarine tunnels, port facilities, various underwater civil engineering structures in canals and waterways, etc.). In view of the effects of the present invention, as the substrate, ships (new ships or ships after operation) are preferred, and large steel ships such as container ships, oil tankers, bulk carriers, etc. that repeatedly sail and anchor for a long time are particularly preferred.

[0182] The substrate may be a substrate treated with a rust inhibitor or other treatment agent, a coating other than an antifouling coating such as an antirust coating (e.g., zinc-rich paint), an anticorrosion coating (e.g., epoxy-based heavy anticorrosion coating), an adhesive coating, etc. formed on the surface (non-antifouling coating), or an antifouling coating of the present invention that has deteriorated, deteriorated, or consumed, or an antifouling coating formed by other antifouling coating compositions (old antifouling coating). In the substrate with an antifouling coating of the present invention, the antifouling coating does not need to be formed in direct contact with the surface of the substrate, and may be formed on the substrate via a treatment agent, other coating, etc. Therefore, the substrate with an antifouling coating of the present invention may contain other treatment agents, coatings, etc. in addition to the substrate and the antifouling coating of the present invention. The antifouling coating of the present invention may be formed on various non-antifouling coatings, deteriorated antifouling coatings, etc.

[0183] The "non-antifouling coating film" possessed by the substrate refers to a coating film other than the antifouling coating film, such as a primer coating film and a mid-coat coating film, which are formed on the substrate in advance before forming the antifouling coating film of the present invention, depending on the type and purpose of the substrate. The type of the non-antifouling coating film is not particularly limited, and examples thereof include: an antirust coating film formed by an antirust paint, an anticorrosion coating film formed by an anticorrosion paint, an adhesive coating film formed by an adhesive coating, etc. As an anticorrosion coating film, for example, an anticorrosion coating film formed by an anticorrosion coating containing an epoxy resin can be cited. As an adhesive coating film, for example, an adhesive coating film formed by an adhesive coating containing one or more resins of epoxy, vinyl, (meth) acrylic, etc. can be cited. It should be noted that when applied to a substrate such as a ship, there is no clear distinction between the anticorrosion coating film (primer coating film) and the adhesive coating film (mid-coat coating film), and sometimes a coating film that combines both is used, but the "non-antifouling coating film" can also be an adhesive coating film that simultaneously has the function of such an anticorrosion coating film.

[0184] The "old antifouling coating" possessed by the substrate refers to an antifouling coating that has been used after being in contact with water (seawater) for a certain period of time (for example, the durability period of the antifouling coating), and is an antifouling coating that is in a state of deterioration, deterioration or consumption compared to the sound antifouling coating before use (before immersion in seawater). The degree of deterioration, deterioration or consumption of the antifouling coating is not particularly limited, as long as it is considered necessary or preferred to form the antifouling coating of the present invention. The type of antifouling coating is not particularly limited, and it can be the antifouling coating of the present invention or other antifouling coatings. As antifouling coatings, for example, hydrolysis type (for example: a coating formed by a silyl ester resin antifouling coating), hydration decomposition type (for example: a coating formed by a vinyl chloride-isobutyl vinyl ether resin antifouling coating) can be cited.

[0185] -Method for producing substrate with antifouling coating film-

[0186] The method for producing a substrate with an antifouling coating film of the present invention comprises the following steps (1) and (2):

[0187] (1) a step of applying the antifouling coating composition of the present invention onto a substrate or impregnating the substrate into a substrate to obtain a coated body or an impregnated body;

[0188] (2) A step of drying the coated body or impregnated body.

[0189] The coating in step (1) can be carried out according to a conventional method, for example, a method of applying the antifouling coating composition to the substrate using an airless sprayer, an air sprayer, a brush, a roller, etc. The impregnation in step (1) can also be carried out according to a conventional method, for example, a method of immersing the substrate in the antifouling coating composition can be used.

[0190] The conditions for coating or impregnation can also be adjusted in consideration of the drying conditions of step (2) so that an antifouling coating film having a target thickness can be formed. For example, an appropriate amount of the antifouling coating composition can be coated or impregnated onto the substrate per unit area so that the thickness of the dried coating film after step (2) becomes 10 to 300 μm, preferably 30 to 200 μm.

[0191] The drying in step (2) can be carried out according to a conventional method at an appropriate temperature and under other conditions for an appropriate time. For example, a method can be mentioned in which the coated body or impregnated body obtained in step (1) is left at room temperature (e.g., 25° C.) for preferably 0.5 to 14 days, more preferably 1 to 7 days. The drying in this step can be carried out under heating or while blowing air.

[0192] Steps (1) and (2) may be repeated as needed. For example, if an antifouling coating film having a desired thickness cannot be formed by performing steps (1) and (2) only once, steps (1) and (2) may be performed a second time after the first time, and steps (1) and (2) may be performed a further necessary number of times.

[0193] In one embodiment of the present invention, the method for producing a substrate with an antifouling coating of the present invention includes a step of applying the antifouling coating composition of the present invention to a substrate having an old antifouling coating or impregnating the substrate having an old antifouling coating to obtain a coated body or an impregnated body as step (1). In this embodiment, a necessary step, such as a step of removing dirt on the surface of the old antifouling coating by washing with water or the like and drying it, may also be included before step (1). It should be noted that when using an existing antifouling coating composition, due to poor adhesion to the old antifouling coating, a step of removing the old antifouling coating is sometimes required, but since the antifouling coating composition of the present invention has excellent adhesion to various old antifouling coatings, such a removal step can be omitted.

[0194] -Antifouling methods for substrates-

[0195] The antifouling method for a substrate of the present invention includes the step of forming the antifouling coating film of the present invention on at least a portion of a substrate.

[0196] The portion of the substrate on which the antifouling coating of the present invention is formed is not particularly limited and can be appropriately selected according to the intended use. For example, when the substrate is a ship, the bottom of the ship (permanently submerged portion) or the waterline (dry-wet alternating portion) exposed to a biofouling environment can be set as the portion (part of the substrate) on which the antifouling coating of the present invention is formed.

[0197] The "step of forming an antifouling coating film" in the "antifouling method for a substrate" is basically the same as the above steps (1) and (2) in the "method for producing a substrate with an antifouling coating film". That is, in other words, the antifouling method for a substrate of the present invention comprises: (1') a step of applying the antifouling coating composition of the present invention to at least a portion of a substrate or impregnating at least a portion of a substrate to obtain a coated body or an impregnated body; and (2') a step of drying the coated body or the impregnated body.

[0198] In addition, in this specification, the technical matters described in the “method for producing a substrate with an antifouling coating film” can be appropriately replaced with the technical matters related to the “antifouling method for a substrate”. For example, in an embodiment in which the substrate is a substrate with a deteriorated antifouling coating film, the “antifouling method for a substrate” of the present invention can be replaced with the “method for repairing a substrate with a deteriorated antifouling coating film”.

[0199] Example

[0200] (1) Production Example of Synthesis of Metal Ester Group-Containing Monomer

[0201] [Manufacturing Example M1] Manufacture of Metal Ester Group-Containing Monomer Mixture Solution (M-1)

[0202] 85.4 parts of PGM (propylene glycol monomethyl ether) and 40.7 parts of zinc oxide were added to a four-necked flask equipped with a cooler, a thermometer, a dropping funnel and a stirrer, and the temperature was raised to 75°C while stirring. Then, a mixture containing 43.1 parts of methacrylic acid, 36.1 parts of acrylic acid and 5 parts of water was added dropwise from the dropping funnel at a constant rate for 3 hours. After further stirring for 2 hours, 36 parts of PGM were added to obtain a transparent metal ester group-containing monomer mixture solution (M-1). The solid content in the solution (M-1) was 44.8% by mass. It should be noted that the solution (M-1) contains zinc diacrylate, zinc dimethacrylate and zinc methacrylate as a mixture of metal ester group-containing monomers (a1) belonging to compound (1').

[0203] [Manufacturing Example M2] Manufacture of Metal Ester Group-Containing Monomer Mixture Solution (M-2)

[0204] 72.4 parts of PGM and 40.7 parts of zinc oxide were added to a four-necked flask equipped with a cooler, a thermometer, a dropping funnel and a stirrer, and the temperature was raised to 75°C while stirring. Then, a mixture containing 30.1 parts of methacrylic acid, 25.2 parts of acrylic acid and 51.6 parts by mass of versatile carbonic acid was uniformly added from the dropping funnel over 3 hours. After further stirring for 2 hours, 11 parts of PGM were added to obtain a transparent metal ester group-containing monomer mixture solution (M-2). The solid content in the solution (M-2) was 59.6% by mass. It should be noted that the solution (M-2) contains zinc diacrylate, zinc dimethacrylate and zinc methacrylate belonging to compound (1'), and zinc (meth)acrylic acid versatile carbonic acid belonging to monomer (2') as a mixture of metal ester group-containing monomers (a1) and (a2).

[0205] [Manufacturing Example M3] Manufacture of Metal Ester Group-Containing Monomer Mixture Solution (M-3)

[0206] Into a four-necked flask equipped with a cooler, a thermometer, a dropping funnel and a stirrer, 59.9 parts of PGM and 40.7 parts of zinc oxide were added, and the temperature was raised to 75°C while stirring. Then, a mixture of 43 parts of methacrylic acid, 36 parts of acrylic acid and 5 parts of water was uniformly added from the dropping funnel over 3 hours. After further stirring for 2 hours, 29.4 parts of PGM were added to obtain a transparent metal ester group-containing monomer mixture solution (M-3). The solid content in the solution (M-3) was 55.1% by mass. It should be noted that the solution (M-3) contains zinc diacrylate, zinc dimethacrylate and zinc methacrylate belonging to compound (1') as a mixture of metal ester group-containing monomers (a1).

[0207] (2) Production Example of Synthesis of Metal Ester Group-Containing Hydrolyzable Copolymer

[0208] [Manufacturing Example A1] Manufacture of hydrolyzable copolymer solution (A-1)

[0209] 15 parts of PGM, 57 parts of xylene and 4 parts of ethyl acrylate (EA) were placed in a four-necked flask equipped with a cooler, a thermometer, a dropping funnel and a stirrer, and the temperature was raised to 100±5° C. while stirring. While maintaining the temperature, 52 parts of the metal ester group-containing monomer mixture solution (M-1), 1 part of methyl methacrylate (MMA), 66.2 parts of ethyl acrylate (EA) and 5.4 parts of 2-methoxyethyl acrylate (MEA), 2.5 parts of polymerization initiator 2,2'-azobisisobutyronitrile, 7 parts of polymerization initiator 2,2'-azobis(2-methylbutyronitrile), 1 part of chain transfer agent "Nofmer MSD" (product name, manufactured by NOF Corporation, α-methylstyrene dimer) and 10 parts of xylene were added dropwise over 6 hours using a dropping funnel. After completion of the dropwise addition, 0.5 parts of a polymerization initiator, tert-butyl peroctoate (TBPO) and 7.0 parts of xylene were added dropwise over 30 minutes, and the mixture was further stirred for 1 hour and 30 minutes. Then, 4.4 parts of xylene was added to obtain a light yellow transparent hydrolyzable copolymer solution (A-1).

[0210] [Manufacturing Example A2] Manufacture of a hydrolyzable copolymer solution (A-2)

[0211] PGM 10 parts, xylene 63 parts and ethyl acrylate (EA) 3 parts were added to a four-necked flask equipped with a cooler, a thermometer, a dropping funnel and a stirrer, and the temperature was raised to 100±5°C while stirring. While maintaining the temperature, 50.3 parts of the metal ester group-containing monomer mixture solution (M-2), 9 parts of methyl methacrylate (MMA), 58 parts of ethyl acrylate (EA), 5 parts of 2,2'-azobis(2-methylbutyronitrile) (AMBN) and PGM 10 parts were added dropwise over 4 hours using a dropping funnel. After the addition was completed, 0.5 parts of tert-butyl peroctoate as a polymerization initiator and 7 parts of xylene were added dropwise over 30 minutes, and the mixture was further stirred for 1 hour and 30 minutes, and then 12 parts of xylene were added to obtain a light yellow transparent hydrolyzable copolymer solution (A-2).

[0212] [Manufacturing Example A3] Manufacture of a hydrolyzable copolymer solution (A-3)

[0213] 10 parts of PGM, 35 parts of xylene and 4 parts of ethyl acrylate (EA) were placed in a pressure polymerization autoclave equipped with a cooler, a thermometer, a drip tank and a stirrer, and the pressure was increased to 350 kPa while stirring, and the temperature was raised to 135° C. Then, 15 parts of methyl methacrylate (MMA), 48 parts of ethyl acrylate (EA), 15 parts of n-butyl acrylate (n-BA), 40 parts of the above-mentioned metal ester group-containing monomer mixture solution (M-3), 10 parts of xylene, 1.8 parts of "Nofmer MSD", 4 parts of 2,2'-azobisisobutyronitrile (AIBN) and 2 parts of 2,2'-azobis(2-methylbutyronitrile) (AMBN) were dripped from the drip tank at a constant speed over 2.5 hours. After the addition was completed, the temperature was lowered to 110°C over 30 minutes, 0.5 parts of t-butyl peroxyoctanoate and 5 parts of xylene were added dropwise over 30 minutes, and the mixture was further stirred for 1 hour and 30 minutes, and then 3 parts of xylene were added. The obtained mixture was filtered through 300 mesh to obtain a light yellow transparent filtrate containing no insoluble matter, which was a hydrolyzable copolymer solution (A-3).

[0214] [Manufacturing Example A4] Manufacture of a hydrolyzable copolymer solution (A-4)

[0215] Into a four-necked flask equipped with a cooler, a thermometer, a dropping funnel and a stirrer, 15 parts of n-butanol, 56 parts of xylene and 4 parts of ethyl acrylate (EA) were placed, and the temperature was raised to 100° C. while stirring. Next, 12.5 parts of n-butyl acrylate (BA), 30.2 parts of methyl methacrylate (MMA), 23.2 parts of ethyl acrylate, 6 parts of 2-methoxyethyl acrylate (2-MEA), 10 parts of "X-22-174ASX" (product name, manufactured by Shin-Etsu Chemical Co., Ltd.), 31.3 parts of the metal ester group-containing monomer mixture solution (M-1), 10 parts of xylene, 0.8 parts of "Nofmer MSD", 1 part of 2,2'-azobisisobutyronitrile (AIBN) and 8 parts of 2,2'-azobis(2-methylbutyronitrile) (AMBN) were added dropwise from the dropping funnel at a constant rate over 6 hours. After completion of the dropwise addition, 2 parts of tert-butyl peroxyoctanoate (TBPO) and 7 parts of xylene were added dropwise over 90 minutes, and the mixture was further stirred for 60 minutes. Thereafter, 7.5 parts of xylene was added to obtain a colorless and transparent hydrolyzable copolymer solution (A-4).

[0216] [Manufacturing Example A5] Manufacture of a hydrolyzable copolymer solution (A-5)

[0217] Into a four-necked flask equipped with a cooler, a thermometer, a dropping funnel and a stirrer, 15 parts of n-butanol, 56 parts of xylene and 4 parts of ethyl acrylate (EA) were placed, and the temperature was raised to 100° C. while stirring. Next, 7.5 parts of n-butyl acrylate (n-BA), 37 parts of methyl methacrylate (MMA), 32 parts of ethyl acrylate (EA), 10 parts of "X-22-174ASX", 21.5 parts of the above metal ester group-containing monomer mixture solution (M-1), 10 parts of xylene, 0.8 parts of "Nofmer MSD", 1 part of 2,2'-azobisisobutyronitrile (AIBN) and 8 parts of 2,2'-azobis(2-methylbutyronitrile) (AMBN) were added dropwise from the dropping funnel at a constant rate over 6 hours. After completion of the dropwise addition, 2 parts of tert-butyl peroxyoctanoate (TBPO) and 7 parts of xylene were added dropwise over 90 minutes, and the mixture was further stirred for 60 minutes. Then, 13 parts of xylene was added to obtain a colorless and transparent hydrolyzable copolymer solution (A-5).

[0218] [Manufacturing Example A6] Manufacture of a hydrolyzable copolymer solution (A-6)

[0219] Into a four-necked flask equipped with a cooler, a thermometer, a dropping funnel and a stirrer, 15 parts of n-butanol, 36 parts of xylene and 4 parts of ethyl acrylate (EA) were placed, and the temperature was raised to 100° C. while stirring. Next, 7.5 parts of n-butyl acrylate (n-BA), 21 parts of methyl methacrylate (MMA), 30.9 parts of ethyl acrylate (EA), 12.5 parts of cyclohexyl methacrylate (CHMA), 10 parts of "X-22-174ASX", 31.3 parts of the above metal ester group-containing monomer mixture solution (M-1), 0.8 parts of "Nofmer MSD", 1 part of 2,2'-azobisisobutyronitrile (AIBN) and 10 parts of 2,2'-azobis(2-methylbutyronitrile) (AMBN) were added dropwise from the dropping funnel at a constant rate over 6 hours. After completion of the dropwise addition, 2 parts of tert-butyl peroxyoctanoate (TBPO) and 7 parts of xylene were added dropwise over 90 minutes, and the mixture was further stirred for 60 minutes. Then, 13.5 parts of xylene was added to obtain a colorless and transparent hydrolyzable copolymer solution (A-6).

[0220] <Measurement of number average molecular weight (Mn) and weight average molecular weight (Mw) of copolymer>

[0221] The number average molecular weight (Mn) and weight average molecular weight (Mw) of the copolymer contained in the hydrolyzable copolymer solutions (A-1) to (A-6) were measured by gel permeation chromatography (GPC) under the following conditions.

[0222] Device: "HLC-8320GPC" (manufactured by Tosoh Corporation)

[0223] Column: "TSKgelG4000HXL G2000HXL" (Made by Tosoh Corporation, size 7.8mmID×30cmL)

[0224] Eluent: THF (1 mmol citric acid)

[0225] Flow rate: 1.000ml / min

[0226] Detector: RI

[0227] Column thermostat temperature: 40°C

[0228] Standard material: polystyrene

[0229] Sample preparation method: 1 mmol of THF (tetrahydrofuran) containing citric acid was added to the copolymer solution prepared in each production example to dilute the solution so that the solid content concentration of the copolymer became 0.4 wt %, and then the solution was filtered with a membrane filter. The filtrate obtained was used as a GPC measurement sample.

[0230] Table 1 shows information (monomers and properties) about the hydrolyzable copolymer solutions (A-1) to (A-6).

[0231]

[0232] (3) Preparation of antifouling coating compositions of Examples 1 to 23 and Comparative Examples 1 to 6

[0233] 6.5 parts of xylene, 3 parts of "propylene glycol monomethyl ether" (product name, propylene glycol monomethyl ether), 0.5 parts of versatile carbonic acid, 1 part of chlorinated paraffin, and 35 parts of hydrolyzable polymer solution (A-3) were added to a plastic container as a solvent, and mixed using a paint shaker until each component was uniformly dispersed or dissolved. Then, 10 parts of talc, 25 parts of zinc oxide, 2 parts of red iron, 5 parts of precipitated barium sulfate, 2 parts of calcined gypsum, 5 parts of copper pyrithione, 0.5 parts of medetomidine, 2.5 parts of bromopyrrole nitrile, and 1 part of oxidized polyethylene wax were further added to the plastic container, and stirred for 1 hour using a paint shaker to disperse these components. After dispersion, 1 part of fatty acid amide wax was further added, and stirred for 20 minutes using a paint shaker, and then the mixture was filtered with a filter (pore size: 80 mesh) to remove the residue, thereby obtaining the metal ester antifouling coating composition of Example 1 as a filtrate.

[0234] Except for changing the compounding amount of each component as described in Table 2, the metal ester antifouling coating compositions of Examples 2 to 23 and Comparative Examples 1 to 6 were obtained by the same preparation method as described above.

[0235] It should be noted that the blending amount of each component described in Table 2 represents the blending amount based on wet weight. For example, the blending amount of the fatty acid amide wax in Example 1 based on wet weight (as a whole) is 1 part, and the solid content is 20% by mass, so the blending amount of the fatty acid amide wax is 0.2 parts.

[0236] (4) Evaluation test

[0237] (4-1) Static antifouling performance after sailing (dynamic immersion)

[0238] A sandblasted steel plate (170 mm long × 70 mm wide × 2.3 mm thick) that had been bent was prepared so that it could be mounted on the side of a rotating drum installed on a test raft tied to Kure Bay in Hiroshima Prefecture. An epoxy-based anticorrosion paint (manufactured by China Paint Co., Ltd., "Banno 500") was applied to the sandblasted steel plate in such a way that its dry film thickness was 150 μm, and then dried at room temperature for 1 day to form a coating film. An epoxy-based adhesive paint (manufactured by China Paint Co., Ltd., "Banno 500N") was applied to the surface of the anticorrosion coating film in such a way that its dry film thickness was 100 μm, and it was dried at room temperature for 1 day. Furthermore, each antifouling coating composition prepared in the examples and comparative examples was applied to the coating film in such a way that its dry film thickness was 100 μm, and it was left at room temperature for 7 days to prepare a test plate 1 with an antifouling coating film.

[0239] First, according to the dynamic antifouling test, the test plate 1 with the antifouling coating is mounted on the rotating drum, and the test plate is rotated continuously for 6 months at a peripheral speed of 10 kt, assuming the actual sailing of the ship, and the entire test plate is dynamically immersed in seawater. Next, the test plate 1 with the antifouling coating after dynamic immersion is placed on a test raft in Hiroshima Bay in such a way that the entire test plate is immersed in seawater, and a static antifouling test for 6 months and 12 months is carried out. The aquatic organism attachment area on each antifouling coating after 6 months and 12 months is measured, and the static antifouling property of the antifouling coating after sailing (dynamic immersion) is evaluated according to the following evaluation criteria for antifouling performance.

[0240] (4-2) Static antifouling performance in wet-dry alternating areas

[0241] An epoxy anticorrosion coating (manufactured by China Paint Co., Ltd., "Banno 500") was applied to a sandblasted steel plate (300 mm long × 100 mm wide × 2.3 mm thick) in a manner that the dry film thickness was 150 μm, and then dried at room temperature for 1 day to form a coating film. An epoxy adhesive coating (manufactured by China Paint Co., Ltd., "Banno 500N") was applied to the surface of the anticorrosion coating film in a manner that the dry film thickness was 100 μm, and dried at room temperature for 1 day. Further, each antifouling coating composition prepared in the examples and comparative examples was applied to the coating film in a manner that the dry film thickness was 100 μm, and dried at room temperature for 7 days to prepare a test plate 2 with an antifouling coating film.

[0242] The test plate 2 with the antifouling coating was placed on a test raft in Hiroshima Bay in such a way that half of the test plate was immersed in seawater, and a static antifouling test was carried out for 6 months and 12 months. The aquatic organism attachment area on each antifouling coating was measured after 6 months and 12 months, and the static antifouling property of the antifouling coating in the wet-dry alternating area was evaluated according to the following evaluation criteria for antifouling performance.

[0243] <Evaluation criteria for antifouling performance / 0, 1, 2 points are considered pass>

[0244] 0: No marine organisms attached

[0245] 1: The attachment area of ​​marine organisms is less than 1% of the total

[0246] 2: The attachment area of ​​marine organisms is more than 1% and less than 10% of the total area

[0247] 3: The attachment area of ​​marine organisms is more than 10% and less than 30% of the total area

[0248] 4: The attachment area of ​​marine organisms is more than 30% and less than 70% of the total

[0249] 5: The attachment area of ​​marine organisms accounts for more than 70% of the total

[0250] (4-3) Adhesion performance on adhesive coating (60°C × 2 days drying)

[0251] An epoxy anticorrosion coating (manufactured by China Paint Co., Ltd., "Banno 500") was applied to a sandblasted steel plate (length 150 mm × width 70 mm × thickness 2.3 mm) in a manner that the dry film thickness was 150 μm, and then dried at room temperature for 1 day to form a coating film. An epoxy adhesive coating (manufactured by China Paint Co., Ltd., "Banno 500N") was applied to the surface of the anticorrosion coating film in a manner that the dry film thickness was 100 μm, and dried at 40°C for 1 day. Further, each antifouling coating composition prepared in the examples and comparative examples was applied to the coating film in a manner that the dry film thickness was 100 μm, and dried at 60°C for 2 days to prepare a test plate 3 with an antifouling coating film.

[0252] Based on 6. Dupont formula of JIS K 5600-5-3: 1999, a weight of 1000 g was dropped from a drop height of 50 cm onto the test plate 3 having the antifouling coating. The cracking of the coating surface after the weight was dropped was visually evaluated according to the following evaluation criteria for adhesion performance.

[0253] <Evaluation criteria for adhesion performance / 0, 1, 2 points are considered pass>

[0254] 0: No cracks or peeling on the coating surface

[0255] 1: Peeling occurs on the coating surface, and the maximum length of peeling measured at the center point of a falling weight is less than 10 mm

[0256] 2: Peeling occurs on the coating surface, with the maximum length being 10 mm or more and less than 20 mm

[0257] 3: Peeling occurs on the coating surface, with the maximum length being 20 mm or more and less than 30 mm

[0258] 4: Peeling occurs on the coating surface, with the maximum length being 30 mm or more and less than 40 mm

[0259] 5: Peeling occurs on the coating surface, and the maximum length is more than 40mm

[0260] (4-4) Adhesion performance on adhesive substrate (immersed in 40°C seawater for 3 months)

[0261] The test plate 2 with the antifouling coating was immersed in natural seawater at 40°C for 3 months, and then cut at 5 mm intervals by a method based on JIS K 5600-5-6:1999, and evaluated according to the following evaluation criteria for adhesion performance.

[0262] <Evaluation criteria for adhesion performance / 0, 1, 2 points are considered pass>

[0263] 0: No stripping

[0264] 1: The peeling area is less than 5% of the whole

[0265] 2: The peeling area is more than 5% and less than 10% of the whole

[0266] 3: The peeling area is more than 10% and less than 30% of the whole

[0267] 4: The peeling area is more than 30% and less than 70% of the whole

[0268] 5: The peeling area is more than 70% of the whole

[0269] (4-5) Deterioration of adhesion performance on the coating film

[0270] An epoxy anticorrosion coating (manufactured by China Paint Co., Ltd., "Banno 500") was applied to a sandblasted steel plate (300 mm long × 100 mm wide × 2.3 mm thick) in a manner that the dry film thickness was 150 μm, and then left at room temperature for 1 day to form a coating film. An epoxy adhesive coating (manufactured by China Paint Co., Ltd., "Banno 500N") was applied to the surface of the anticorrosion coating film in a manner that the dry film thickness was 100 μm, and left to dry at room temperature for 1 day. Further, each silyl ester resin antifouling coating composition, vinyl chloride-isobutyl vinyl ether resin antifouling coating composition, and the antifouling coating composition prepared in the examples and comparative examples were applied to the coating film in a manner that the dry film thickness was 100 μm, dried at room temperature for 7 days, and then immersed in natural seawater at 40°C for 3 months to prepare test plates 1 to 3 with deteriorated coating films.

[0271] At 80kgf / cm 2 The test plates 1 to 3 with the deteriorated coating film were washed with water at a pressure of , and dried at room temperature for 7 days. Then, the coating composition of each embodiment and comparative example was applied on each deteriorated coating film, and dried at room temperature for 7 days to prepare test plates with antifouling coating films on the deteriorated coating films. These test plates were immersed in seawater at 40°C for 3 months, and then cut at intervals of 5 mm by a method based on JIS K 5600-5-6:1999, and evaluated according to the following evaluation criteria for adhesion performance.

[0272] <Evaluation criteria for adhesion performance / 0, 1, 2 points are considered pass>

[0273] 0: No stripping

[0274] 1: The peeling area is less than 5% of the whole

[0275] 2: The peeling area is more than 5% and less than 10% of the whole

[0276] 3: The peeling area is more than 10% and less than 30% of the whole

[0277] 4: The peeling area is more than 30% and less than 70% of the whole

[0278] 5: The peeling area is more than 70% of the whole

[0279] It should be noted that the silyl ester resin antifouling coating composition was prepared according to the following Production Example X, and the vinyl chloride-isobutyl vinyl ether resin antifouling coating composition was prepared according to the following Production Example Y. The test plate 1 with a deteriorated coating film refers to a test plate formed with a silyl ester resin antifouling coating film, the test plate 2 with a deteriorated coating film refers to a test plate formed with a vinyl chloride-isobutyl vinyl ether resin antifouling coating film, and the test plate 3 with a deteriorated coating film refers to a test plate formed with the antifouling coating films described in the Examples and Comparative Examples.

[0280] [Manufacturing Example X] Silyl ester resin antifouling coating composition

[0281] The following reaction was carried out under normal pressure and nitrogen atmosphere. 428.6 parts of xylene and 100 parts of triisopropylsilyl methacrylate (TIPSMA) were added to a reaction container equipped with a stirrer, a reflux condenser, a thermometer, a nitrogen inlet tube and a dropping funnel, and heated to a liquid temperature of 80°C while stirring with a stirrer. While the liquid temperature in the reaction container was maintained at 80±5°C, a mixture containing 500 parts of triisopropylsilyl methacrylate (TIPSMA), 250 parts of 2-methoxyethyl methacrylate (MEMA), 100 parts of methyl methacrylate (MMA), 50 parts of butyl acrylate (BA) and 13 parts of 2,2'-azobisisobutyronitrile (AIBN) was added dropwise from the dropping funnel to the reaction container over 2 hours. After the addition was completed, the reaction solution was stirred at 80°C for 1 hour and at 80-95°C for 1 hour and 30 minutes. Then, 1 part of AIBN was added to the reaction solution 4 times every 30 minutes while maintaining 95°C, and the liquid temperature was raised to 105°C to complete the polymerization reaction. Next, 238 parts of xylene were added to the reaction container, and the mixture was stirred until the liquid became uniform, thereby obtaining a copolymer solution (X1) having a solid content of 61.1% by mass and a viscosity of 1498 mPa·s. The Mw of the copolymer contained in the copolymer solution (X1) was 31213.

[0282] 8.5 parts of xylene as a solvent, 1 part of an aromatic hydrocarbon solvent (Solvesso No. 100, manufactured by Exxon Mobil), 2.5 parts of rosin, 0.5 parts of alkoxysilane (Ethyl Silicate 28, manufactured by Colcoat), and 21 parts of the copolymer solution (X1) were added to a plastic container, and mixed using a paint shaker until the components were uniformly dispersed or dissolved. Then, 4 parts of talc, 4 parts of zinc oxide, 50 parts of cuprous oxide (NC-301), 1.5 parts of iron oxide, 2.5 parts of titanium oxide (Tipaque PFC105, manufactured by Ishihara Sangyo Co., Ltd.), 2 parts of copper pyrithione, and 1 part of oxidized polyethylene wax were further added to the plastic container, and stirred using a paint shaker for 1 hour to disperse these components. After dispersion, 1.5 parts of fatty acid amide wax was further added and stirred for 20 minutes using a paint shaker. The mixture was then filtered through a filter (pore size: 80 mesh) to remove the residue to obtain a silyl ester antifouling coating composition as a filtrate.

[0283] [Manufacturing Example Y] Vinyl chloride-isobutyl vinyl ether resin antifouling coating composition

[0284] 13 parts of xylene, 3 parts of 2-heptanone, 9 parts of rosin, 3 parts of tricresyl phosphate (TCP, manufactured by Kyowa Hakko Kogyo Co., Ltd.), and 5 parts of vinyl chloride-isobutyl vinyl ether copolymer (Laroflex MP25, manufactured by BASF) as solvents were added to a plastic container, and a paint shaker was used to mix until each component was uniformly dispersed or dissolved. Then, 10 parts of talc, 3 parts of zinc oxide, 42 parts of cuprous oxide (Red Copp 97N Premium, manufactured by American Chemet Corp.), 4 parts of titanium oxide, and 5 parts of DCOIT (SEA NINE 211N, manufactured by Rohm and Haas Japan Co., Ltd., solid content 30%) were further added to the plastic container, and the paint shaker was used to stir for 1 hour to disperse these components. After dispersion, 3 parts of fatty acid amide wax were further added, and the paint shaker was used to stir for 20 minutes, and then the mixture was filtered with a filter (pore size: 80 meshes) to remove the residue to obtain a vinyl chloride-isobutyl vinyl ether antifouling coating composition as a filtrate.

[0285] Information (compositions and evaluation test results) on the antifouling coating compositions of Examples 1 to 23 and Comparative Examples 1 to 6 are shown in Table 2. In addition, Table 3 shows details of the components (products) described in Table 2 used in the preparation of these antifouling coating compositions.

[0286]

[0287]

[0288]

[0289]

[0290]

[0291] By comparing the results of the evaluation tests of Examples and Comparative Examples described in Table 2, for example, the following results can be obtained.

[0292] (1) Comparison of Comparative Example 1 containing bromopyrrolecarbonitrile (C) and copper pyrithione (D) as antifouling agents but not containing medetomidine (B) with Examples 1, 2 and 4 containing all medetomidine (B), bromopyrrolecarbonitrile (C) and copper pyrithione (D) and having the same components as Comparative Example 1 shows that, compared with conventional antifouling coating compositions such as the former, the antifouling coating composition of the present invention having the constituent elements such as the latter can form an antifouling coating film which is excellent in static antifouling property after long-term dynamic immersion and in static antifouling property in a wet-dry cycle without impairing the performance of other evaluation tests. In addition, the latter antifouling coating film is also excellent in adhesion to a deteriorated antifouling coating film of a vinyl chloride-isobutyl vinyl ether resin compared with the former antifouling coating film.

[0293] (2) Comparison of Comparative Example 4 containing medetomidine (B) and copper pyrithione (D) as antifouling agents but not containing bromopyrrolecarbonitrile (C) with Examples 2, 5 and 6 containing all medetomidine (B), bromopyrrolecarbonitrile (C) and copper pyrithione (D) and having the same components as Comparative Example 4 shows that the antifouling coating composition of the present invention having the constituent elements of the latter can form an antifouling coating film having excellent static antifouling properties after long-term dynamic immersion and static antifouling properties in a wet-dry cycle without impairing the performance of other evaluation tests, compared with the conventional antifouling coating composition of the former. In addition, the latter antifouling coating film also has excellent adhesion to a deteriorated antifouling coating film of a vinyl chloride-isobutyl vinyl ether resin, compared with the former antifouling coating film.

[0294] (3) Comparison between Comparative Example 5 which does not contain a linear or branched alkyl carboxylic acid (E) having 4 to 30 carbon atoms (tert-carbonic acid as a representative example thereof) and Examples 2, 9 and 10 which contain an alkyl carboxylic acid (E) and have the same components as Comparative Example 9 shows that, compared with conventional antifouling coating compositions such as the former, the antifouling coating composition of the present invention having the constituent elements such as the latter can form an antifouling coating film which has excellent adhesion to deteriorated antifouling coating films of silyl ester resins and deteriorated antifouling coating films of vinyl chloride-isobutyl vinyl ether resins (i.e., old antifouling coating films other than the same antifouling coating film) and also has excellent adhesion to epoxy adhesive coating films without impairing the performance of other evaluation tests.

[0295] (4) As can be seen from the comparison between Comparative Example 3 which does not contain copper pyrithione (D) but contains zinc pyrithione and Example 2 which contains copper pyrithione (D) but does not contain zinc pyrithione and has the same components as Comparative Example 3, the antifouling coating composition of the present invention having the constituent elements of the latter can form an antifouling coating film which has excellent adhesion to deteriorated antifouling coating films of silyl ester resins and deteriorated antifouling coating films of vinyl chloride-isobutyl vinyl ether resins (i.e., old antifouling coating films other than the same antifouling coating film) without impairing the performance of other evaluation tests, and also has excellent adhesion to epoxy adhesive coating films.

[0296] (5) Comparison between Comparative Example 6 which does not contain a linear or branched alkyl carboxylic acid (E) having 4 to 30 carbon atoms (tert-carbonic acid as a representative example thereof) but contains rosin and Example 2 which contains a linear or branched alkyl carboxylic acid (E) having 4 to 30 carbon atoms (tert-carbonic acid as a representative example thereof) but does not contain rosin and has the same components as Comparative Example 6, shows that the antifouling coating composition of the present invention having the constituent elements of the latter can form an antifouling coating film which has significantly better adhesion to a deteriorated antifouling coating film of a silyl ester resin type and a deteriorated antifouling coating film of a vinyl chloride-isobutyl vinyl ether resin type (i.e., an old antifouling coating film other than the same antifouling coating film), has better adhesion to the same deteriorated antifouling coating film, and has significantly better adhesion to an epoxy adhesive coating film, as compared to the conventional antifouling coating composition of the former.

Claims

1. An antifouling coating composition comprising a hydrolyzable polymer containing a metal ester group (A), medetomidine (B), bromopyrrole carbonitrile (C), copper pyrithione (D), and a linear or branched alkyl carboxylic acid having 4 to 30 carbon atoms (E), The polymer (A) comprises a structural unit derived from a metal ester group-containing monomer (a1) represented by the following formula (1) and / or a structural unit derived from a metal ester group-containing monomer (a2) represented by the following formula (2), In formula (1), R 11 Each independently represents a monovalent group containing a terminal ethylenically unsaturated group, M represents a copper atom or a zinc atom, In formula (2), R 21 represents a monovalent group containing a terminal ethylenically unsaturated group, R 22 represents a monovalent organic group having 1 to 30 carbon atoms and having no terminal ethylenically unsaturated group, and M represents a copper atom or a zinc atom.

2. The antifouling coating composition according to claim 1, wherein The polymer (A) comprises a metal ester group-containing monomer (a1) represented by the following formula (1'): In formula (1'), R 12 Each independently represents a hydrogen atom or a methyl group, and M represents a copper atom or a zinc atom.

3. The antifouling coating composition according to claim 1 or 2, wherein: The alkyl carboxylic acid (E) is tertiary carbonic acid.

4. The antifouling coating composition according to claim 1 or 2, wherein With respect to 100% by mass of the copper pyrithione (D), the content of the medetomidine (B) is 0.1 to 100% by mass, the content of the bromopyrrole carbonitrile (C) is 10 to 1700% by mass, and The content of copper pyrithione (D) is 0.5 to 12% by mass based on 100% by mass of the solid content of the antifouling coating composition.

5. An antifouling coating film formed from the antifouling coating composition according to claim 1 or 2. 6 . A substrate with an antifouling coating film, comprising a substrate and the antifouling coating film according to claim 5 .

7. The substrate with an antifouling coating according to claim 6, wherein The substrate is selected from the group consisting of ships, underwater structures and fishery materials.

8. A method for producing a substrate with an antifouling coating, comprising: A step (1) of coating the antifouling coating composition according to claim 1 or 2 on a substrate or impregnating the substrate into a substrate to obtain a coated body or an impregnated body; and A step (2) of drying the coated body or impregnated body. 9 . An antifouling method for a substrate, comprising the step of forming the antifouling coating film according to claim 5 on at least a portion of a substrate.

Citation Information

Patent Citations

  • Anti-fouling coating composition

    JP2020100794A

  • Antifouling coating composition and use for same

    WO2011118526A1

  • Antifouling coating composition, antifouling coating film, substrate having antifouling coating film, antifouling substrate, method for producing substrate having antifouling coating film, and method for preventing fouling of substrate

    WO2016084769A1

  • Antifouling coating material composition, antifouling coating film, substrate provided with antifouling coating film and production method therefor, and antifouling method

    WO2018003135A1

  • Antifouling coating composition, antifouling coating film, substrate having antifouling coating film, antifouling substrate, method for producing substrate having antifouling coating film, and method for preventing fouling of substrate

    CN107001845A